Transnational Metropolitan Development Strategies and Governance in a Post-Socialist Setting: The Case of Szczecin - Tölle, Alexander (Quaestiones Geographicae, 2014)
The integration of cities and their regions into transnational networks has become a key municipal strategy, with the creation of a metropolitan governance structure being seen in this context as a fundamental element. The Szczecin Metropolitan Area constitutes an example of meagre results in intercommunal cooperation in post-socialist East-Central Europe. This has its repercussions on the task of creating cross-border metropolitan governance structures including adjacent German counties, a task which, in turn, may help to overcome development barriers. This becomes apparent particularly in the process of defining joint development objectives as well as an image for the cross-border metropolitan region